Fibrous carbon nanostructures and method for producing surface-modified fibrous carbon nanostructures

JP7632305B2Active Publication Date: 2025-02-19ZEON CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021567315
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-27
Filing Date
2020-12-15
Publication Date
2025-02-19
Estimated Expiration
2040-12-15

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、表面改質処理後の分散性に優れた繊維状炭素ナノ構造体を提供することができる。 また、本発明によれば、分散性に優れた表面改質繊維状炭素ナノ構造体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632305000001
    Figure 0007632305000001
Patent Text Reader

Abstract

The purpose of the present invention is to provide a fibrous carbon nanostructure which can have excellent dispersibility after the fibrous carbon nanostructure undergoes a surface modification treatment. The fibrous carbon nanostructure of the present invention is characterized in that the amount of localized electrons, which is determined by an electron spin resonance measurement at a temperature of 10K, is 1.0×1017 / g or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fibrous carbon nanostructure and a method for producing a surface-modified fibrous carbon nanostructure. [Background technology]

[0002] In recent years, fibrous carbon nanostructures such as carbon nanotubes (hereinafter sometimes referred to as "CNTs") have been attracting attention as materials with excellent electrical conductivity, thermal conductivity and mechanical properties.

[0003] However, fibrous carbon nanostructures such as CNTs tend to form bundle structures due to van der Waals forces and are difficult to disperse in a solvent, and therefore may not be able to fully exhibit properties such as electrical conductivity.

[0004] Therefore, there has been active development of techniques for obtaining surface-modified fibrous carbon nanostructures with improved dispersibility by subjecting fibrous carbon nanostructures such as CNTs to various surface modification treatments.

[0005] For example, Patent Document 1 proposes a technology for improving the dispersibility of CNTs in a solvent by performing a liquid-phase oxidation treatment as a surface modification treatment on CNTs that have an intensity ratio between the G band and the D band (G / D ratio) of 50 or more in Raman spectroscopy. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2018 / 043487 Summary of the Invention [Problem to be solved by the invention]

[0007] However, the inventors have found through their investigations that the fibrous carbon nanostructures used in the above-mentioned surface modification treatments of the prior art have room for improvement in terms of dispersibility after the surface modification treatment.

[0008] Therefore, an object of the present invention is to provide a fibrous carbon nanostructure that has excellent dispersibility after surface modification treatment. Another object of the present invention is to provide a surface-modified fibrous carbon nanostructure having excellent dispersibility. [Means for solving the problem]

[0009] The present inventors have conducted extensive research to achieve the above object, and have found that fibrous carbon nanostructures having a localized electron amount equal to or greater than a predetermined value as determined by electron spin resonance measurement at a temperature of 10 K exhibit excellent dispersibility after surface modification treatment, thereby completing the present invention.

[0010] That is, the present invention has an object to advantageously solve the above-mentioned problems, and the fibrous carbon nanostructure of the present invention has a localized electron amount of 1.0×10 as measured by electron spin resonance at a temperature of 10 K. 17 Thus, the fibrous carbon nanostructure having a localized electron quantity equal to or greater than a predetermined value as determined by electron spin resonance measurement at a temperature of 10 K has excellent dispersibility after surface modification treatment. In the present invention, the amount of localized electrons obtained by electron spin resonance measurement of the fibrous carbon nanostructure at a temperature of 10 K can be measured by the method described in the Examples of this specification.

[0011] Here, the fibrous carbon nanostructure of the present invention preferably has a ratio of G band peak intensity to D band peak intensity in a Raman spectrum (G / D ratio) of 0.5 or more and 5.0 or less. By setting the G / D ratio within the above-mentioned predetermined range, the dispersibility of the fibrous carbon nanostructure after the surface modification treatment can be further improved. This allows the fibrous carbon nanostructure to exhibit particularly excellent properties (e.g., electrical conductivity, thermal conductivity, strength, etc., hereinafter sometimes simply referred to as "properties") after the surface modification treatment. In the present invention, the ratio of the G band peak intensity to the D band peak intensity in a Raman spectrum (G / D ratio) can be measured by the method described in the Examples of this specification.

[0012] In addition, in the fibrous carbon nanostructure of the present invention, the localized electron quantity is 1.0×10 19 When the amount of localized electrons is less than the above-mentioned predetermined value, disappearance of the fibrous carbon nanostructure after the surface modification treatment can be suppressed when the fibrous carbon nanostructure is subjected to the surface modification treatment, and the surface-modified fibrous carbon nanostructure can be efficiently obtained.

[0013] Furthermore, in the fibrous carbon nanostructure of the present invention, it is preferable that the t-plot obtained from the adsorption isotherm shows an upwardly convex shape. If the t-plot obtained from the adsorption isotherm shows an upwardly convex shape, the fibrous carbon nanostructure can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment.

[0014] In addition, the fibrous carbon nanostructure of the present invention preferably contains carbon nanotubes. If the fibrous carbon nanostructure contains carbon nanotubes, excellent properties can be exhibited when the dispersibility is increased by a surface modification treatment.

[0015] Furthermore, in the fibrous carbon nanostructure of the present invention, the carbon nanotubes preferably include single-walled carbon nanotubes. When the fibrous carbon nanostructure includes single-walled carbon nanotubes as the carbon nanotubes, it is possible to exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment.

[0016] The present invention also aims to advantageously solve the above problems, and the method for producing a surface-modified fibrous carbon nanostructure of the present invention is characterized by comprising a step of subjecting any of the above-mentioned fibrous carbon nanostructures to a surface modification treatment to obtain a surface-modified fibrous carbon nanostructure. According to the method for producing a surface-modified fibrous carbon nanostructure of the present invention, it is possible to produce a surface-modified fibrous carbon nanostructure with excellent dispersibility.

[0017] In the method for producing a surface-modified fibrous carbon nanostructure of the present invention, the surface modification treatment is preferably a wet oxidation treatment. If a wet oxidation treatment is used as the surface modification treatment, the dispersibility of the produced surface-modified fibrous carbon nanostructure can be further improved. Effect of the Invention

[0018] According to the present invention, it is possible to provide a fibrous carbon nanostructure having excellent dispersibility after surface modification treatment. Furthermore, according to the present invention, it is possible to provide a surface-modified fibrous carbon nanostructure having excellent dispersibility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention will be described in detail.

[0020] (fibrous carbon nanostructures) The fibrous carbon nanostructure of the present invention is characterized in that the amount of localized electrons obtained by electron spin resonance measurement at a temperature of 10K is a predetermined value or more. Since the amount of localized electrons of the fibrous carbon nanostructure of the present invention is a predetermined value or more, it has excellent dispersibility after surface modification treatment. Therefore, the surface-modified fibrous carbon nanostructure obtained by subjecting the fibrous carbon nanostructure of the present invention to surface modification treatment can exhibit excellent dispersibility in a solvent such as water. Therefore, when various molded products (for example, films such as antistatic films and conductive films) are formed using a dispersion of the obtained surface-modified fibrous carbon nanostructure, the amount of aggregates in the molded product can be reduced. Therefore, the molded product made of the formed surface-modified fibrous carbon nanostructure has excellent properties such as electrical conductivity, thermal conductivity, and strength. In other words, it can be said that the surface-modified carbon nanostructure obtained by subjecting the fibrous carbon nanostructure of the present invention to surface modification treatment has excellent properties as described above.

[0021] Here, the fibrous carbon nanostructure is not particularly limited, and examples thereof include cylindrical carbon nanostructures such as CNTs, and non-cylindrical carbon nanostructures such as carbon nanostructures in which a carbon hexagonal network is formed in a flattened cylinder. The fibrous carbon nanostructure of the present invention may contain one or more of the above-mentioned carbon nanostructures.

[0022] The fibrous carbon nanostructure preferably contains CNT. This is because CNT can exhibit excellent properties (e.g., electrical conductivity, thermal conductivity, strength, etc.) when the dispersibility is increased by a surface modification treatment. The fibrous carbon nanostructure containing CNT may be composed of only CNT, or may be a mixture of CNT and a fibrous carbon nanostructure other than CNT.

[0023] The CNT is not particularly limited, and single-walled carbon nanotubes and / or multi-walled carbon nanotubes can be used. The CNT is preferably a single-walled to five-walled carbon nanotube, and more preferably a single-walled carbon nanotube. This is because the fewer the number of walls of the CNT, the more excellent the properties can be exhibited when the dispersibility is increased by surface modification treatment.

[0024] Here, the fibrous carbon nanostructure of the present invention has a localized electron amount of 1.0×10 17 It is necessary that the number of particles per gram is 3.0×10 17 It is preferable that the number of particles is 5.0×10 17 More preferably, it is 1.0×10 18 More preferably, the number is 5.6×10 18 More preferably, the number is 1.0×10 19 It is preferable that the number of particles is less than 8.0×10 18 It is more preferable that the number of localized electrons is less than 1 / g. When the amount of localized electrons obtained by electron spin resonance measurement at a temperature of 10K is equal to or more than the lower limit, the dispersibility of the fibrous carbon nanostructure after surface modification can be sufficiently improved. On the other hand, when the amount of localized electrons obtained by electron spin resonance measurement at a temperature of 10K is equal to or less than the upper limit, disappearance of the fibrous carbon nanostructure after surface modification can be suppressed when the fibrous carbon nanostructure is subjected to surface modification, and the surface-modified fibrous carbon nanostructure can be efficiently obtained.

[0025] The amount of localized electrons obtained by electron spin resonance measurement of the fibrous carbon nanostructure at a temperature of 10 K can be adjusted by the film thickness of the thin iron film (catalyst layer) in the catalyst substrate used in the manufacturing method of the fibrous carbon nanostructure.

[0026] The average diameter of the fibrous carbon nanostructure is preferably 1 nm or more, and preferably 60 nm or less. The average diameter of the fibrous carbon nanostructure may be 2 nm or more, 3 nm or more, 30 nm or less, 10 nm or less, or 5 nm or less. The fibrous carbon nanostructure having an average diameter within the above-mentioned range can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. The "average diameter of fibrous carbon nanostructures" can be determined by measuring the diameter (outer diameter) of, for example, 20 fibrous carbon nanostructures on a transmission electron microscope (TEM) image and calculating the number-average value.

[0027] As the fibrous carbon nanostructure, it is preferable to use a fibrous carbon nanostructure having a ratio (3σ / Av) of the standard deviation of the diameter (σ: sample standard deviation) multiplied by 3 to the average diameter (Av) of more than 0.20 and less than 0.80, more preferably a fibrous carbon nanostructure having a 3σ / Av of more than 0.25, and even more preferably a fibrous carbon nanostructure having a 3σ / Av of more than 0.50. Fibrous carbon nanostructures having a 3σ / Av of more than 0.20 and less than 0.80 can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. The average diameter (Av) and standard deviation (σ) of the fibrous carbon nanostructures may be adjusted by changing the manufacturing method or manufacturing conditions of the fibrous carbon nanostructures, or by combining multiple types of fibrous carbon nanostructures obtained by different manufacturing methods.

[0028] Furthermore, the average length of the fibrous carbon nanostructure is preferably 10 μm or more, more preferably 50 μm or more, and even more preferably 80 μm or more, and is preferably 600 μm or less, more preferably 550 μm or less, and even more preferably 500 μm or less. The fibrous carbon nanostructure having an average length within the above-mentioned range can exhibit particularly excellent properties when its dispersibility is enhanced by a surface modification treatment. In the present invention, the "average length of fibrous carbon nanostructures" can be determined by measuring the lengths of, for example, 20 fibrous carbon nanostructures on a scanning electron microscope (SEM) image and calculating the number-average value.

[0029] Here, the fibrous carbon nanostructure usually has an aspect ratio of more than 10. The aspect ratio of the fibrous carbon nanostructure can be determined by measuring the diameter and length of 20 randomly selected fibrous carbon nanostructures using a scanning electron microscope or a transmission electron microscope and calculating the average value of the ratio of the diameter to the length (length / diameter).

[0030] The BET specific surface area of ​​the fibrous carbon nanostructure is 600m 2 / g or more, and 2 / g or more is more preferable, and 2000m 2 / g or less, and 2 / g or less is more preferable, and 1600m 2 / g or less is more preferable, 2 / g or less, 1000m 2 / g or less. The BET specific surface area is 600 m 2 Fibrous carbon nanostructures with a BET specific surface area of ​​2000 m or more can exhibit particularly excellent properties when their dispersibility is improved by surface modification treatment. 2 The fibrous carbon nanostructure having a particle size of 100 nm or less can exhibit even better dispersibility after the surface modification treatment.

[0031] In addition, it is preferable that the fibrous carbon nanostructure has a t-plot obtained from the adsorption isotherm that shows an upwardly convex shape. The fibrous carbon nanostructure having a t-plot that shows an upwardly convex shape can exhibit particularly excellent properties when the dispersibility is enhanced by a surface modification treatment. Furthermore, it is more preferable that the fibrous carbon nanostructure has not been subjected to an opening treatment and has a t-plot that shows an upwardly convex shape. The "t-plot" can be obtained by converting the relative pressure into the average thickness t (nm) of the nitrogen gas adsorption layer in the adsorption isotherm of the fibrous carbon nanostructure measured by the nitrogen gas adsorption method. That is, the t-plot of the fibrous carbon nanostructure can be obtained by determining the average thickness t of the nitrogen gas adsorption layer corresponding to the relative pressure from a known standard isotherm in which the average thickness t of the nitrogen gas adsorption layer is plotted against the relative pressure P / P0, and performing the above conversion (t-plot method by de Boer et al.). Here, in a material having pores on the surface, the growth of a nitrogen gas adsorption layer is classified into the following processes (1) to (3). The slope of the t-plot changes depending on the processes (1) to (3) below. (1) The process of forming a monolayer of nitrogen molecules on the entire surface (2) Formation of multilayer adsorption and the associated capillary condensation filling process in the pores (3) The formation of multilayer adsorption on an apparently non-porous surface whose pores are filled with nitrogen

[0032] In the t-plot showing an upward convex shape, the plot is located on a straight line passing through the origin in the region where the average thickness t of the nitrogen gas adsorption layer is small, whereas as t increases, the plot shifts downward from the straight line. Fibrous carbon nanostructures having such a t-plot shape have a large ratio of the internal specific surface area to the total specific surface area of ​​the fibrous carbon nanostructure, indicating that a large number of openings are formed in the carbon nanostructures that make up the fibrous carbon nanostructure.

[0033] The inflection point of the t-plot of the fibrous carbon nanostructure is preferably in the range of 0.2≦t(nm)≦1.5, more preferably in the range of 0.45≦t(nm)≦1.5, and even more preferably in the range of 0.55≦t(nm)≦1.0. Fibrous carbon nanostructures having the inflection point of the t-plot within the above-mentioned range can exhibit particularly excellent properties when the dispersibility is enhanced by a surface modification treatment.

[0034] Here, the "position of the bending point" is the intersection point between the approximation line A in the above-mentioned process (1) and the approximation line B in the above-mentioned process (3).

[0035] Furthermore, the ratio (S2 / S1) of the internal specific surface area S2 to the total specific surface area S1 obtained from the t-plot of the fibrous carbon nanostructure is preferably 0.05 or more, more preferably 0.07 or more, even more preferably 0.10 or more, and preferably 0.30 or less. The fibrous carbon nanostructure having the value of S2 / S1 within the above-mentioned range can exhibit particularly excellent properties when the dispersibility is enhanced by a surface modification treatment.

[0036] Here, the total specific surface area S1 and the internal specific surface area S2 of the fibrous carbon nanostructure can be obtained from the t-plot. Specifically, first, the total specific surface area S1 can be obtained from the slope of the approximation line in step (1), and the external specific surface area S3 can be obtained from the slope of the approximation line in step (3). Then, the internal specific surface area S2 can be calculated by subtracting the external specific surface area S3 from the total specific surface area S1.

[0037] Incidentally, the measurement of the adsorption isotherm of the fibrous carbon nanostructure, the creation of t-plots, and the calculation of the total specific surface area S1 and the internal specific surface area S2 based on the analysis of the t-plots can be performed, for example, using a commercially available measuring device, "BELSORP (registered trademark)-mini" (manufactured by BEL Japan Co., Ltd.).

[0038] Furthermore, the fibrous carbon nanostructure containing CNTs suitable for the fibrous carbon nanostructure preferably has a radial breathing mode (RBM) peak when evaluated by Raman spectroscopy. Note that the Raman spectrum of a fibrous carbon nanostructure consisting only of multi-walled carbon nanotubes having three or more walls does not have an RBM.

[0039] In addition, the fibrous carbon nanostructure preferably has a ratio of G band peak intensity to D band peak intensity in a Raman spectrum (G / D ratio) of 0.5 to 5.0. The G / D ratio may be 1.5 or more, 2.0 or more, 2.5 or more, or 3.0 or more, or 4.5 or less, 4.0 or less, or 3.4 or less. The fibrous carbon nanostructure having a G / D ratio of 0.5 to 5.0 can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment.

[0040] The carbon purity of the fibrous carbon nanostructure is preferably 98% by mass or more, more preferably 99% by mass or more, and further preferably 99.9% by mass or more. The "carbon purity" can be determined using the method described in the Examples of this specification.

[0041] (Method of manufacturing fibrous carbon nanostructures) The above-mentioned fibrous carbon nanostructure of the present invention can be efficiently produced, for example, by a method in which raw material compounds and a carrier gas are supplied onto a substrate (catalyst substrate) having a catalyst layer on its surface, and a fibrous carbon nanostructure is synthesized by a CVD method, in which the catalytic activity of the catalyst layer is dramatically improved by having a trace amount of oxidant (catalyst activation material) present in the system (see, for example, International Publication No. 2006 / 011655), in which the catalyst layer is formed on the substrate surface by a wet process, and a raw material gas containing ethylene as the raw material compound (for example, a gas containing more than 10 volume % ethylene) is used.

[0042] Here, before the synthesis step of supplying raw material compounds and carrier gas onto the catalyst base and synthesizing fibrous carbon nanostructures by CVD, a formation step may be optionally performed in which the surrounding environment of the catalyst layer (for example, within a range of 5 cm or less away from the catalyst layer) is made into a reducing gas environment and the catalyst layer and / or the reducing gas is heated. By performing the formation step, at least one of the following effects can be obtained: reduction of the catalyst in the catalyst layer, promotion of catalyst microparticulation (to create a state suitable for the growth of carbon structures), and improvement of catalyst activity. After the synthesis step, a cooling step may be optionally performed in which the synthesized fibrous carbon nanostructure and the catalyst layer are cooled under an inert gas, which can prevent the fibrous carbon nanostructure and the catalyst in the catalyst layer from being oxidized. The formation process and the cooling process can be carried out, for example, according to the descriptions in International Publication No. 2014 / 208097 and Japanese Patent Application Laid-Open No. 2011-219316.

[0043] The catalyst substrate used in the above-mentioned method for producing a fibrous carbon nanostructure has, for example, a catalyst layer and a catalyst support layer supporting the catalyst layer on a substrate. The catalyst layer is preferably an iron thin film, and the catalyst support layer is preferably an aluminum thin film. Here, the "iron thin film" refers to a thin film containing metallic iron and / or an iron compound, and the "aluminum thin film" refers to a thin film containing metallic aluminum and / or an aluminum compound.

[0044] In the manufacture of the catalyst substrate having the above-mentioned catalyst layer, the catalyst layer can be formed on the substrate surface by a wet process, for example, by applying a coating liquid A containing an aluminum compound onto the substrate, drying the coating of coating liquid A to form a thin aluminum film (catalyst-supported layer) on the substrate, and further applying a coating liquid B containing an iron compound onto the thin aluminum film, and then drying the coating of coating liquid B to form a thin iron film (catalyst layer) on the thin aluminum film.

[0045] Examples of the substrate that can be used herein include substrates made of metals such as iron, nickel, chromium, molybdenum, tungsten, titanium, aluminum, manganese, cobalt, copper, silver, gold, platinum, niobium, tantalum, lead, zinc, gallium, indium, germanium, and antimony; substrates made of alloys or oxides of these metals; substrates made of non-metals such as silicon, quartz, glass, mica, graphite, and diamond; and substrates made of ceramics.

[0046] Furthermore, an aluminum compound such as an organoaluminum compound and / or an aluminum salt capable of forming an alumina thin film as the aluminum thin film, dissolved or dispersed in an organic solvent, can be used as the coating solution A. The concentration of the aluminum compound in the coating solution A can be appropriately adjusted within a range in which the desired effects of the present invention can be obtained.

[0047] Here, examples of organoaluminum compounds capable of forming an alumina thin film include aluminum alkoxides such as aluminum trimethoxide, aluminum triethoxide, aluminum tri-n-propoxide, aluminum tri-i-propoxide, aluminum tri-n-butoxide, aluminum tri-sec-butoxide, and aluminum tri-tert-butoxide. Other examples of organoaluminum compounds capable of forming an alumina thin film include aluminum complexes such as tris(acetylacetonato)aluminum(III). Examples of aluminum salts capable of forming an alumina thin film include aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum bromide, aluminum iodide, aluminum lactate, basic aluminum chloride, and basic aluminum nitrate. These aluminum compounds may be used alone or in combination of two or more.

[0048] As the organic solvent, for example, organic solvents such as alcohols, glycols, ketones, ethers, esters, hydrocarbons, etc. These organic solvents may be used alone or in combination.

[0049] Furthermore, an organic iron compound capable of forming an iron thin film and / or an iron compound such as an iron salt dissolved or dispersed in an organic solvent can be used as Coating Liquid B. The concentration of the iron compound in Coating Liquid B can be appropriately adjusted within a range in which the desired effects of the present invention can be obtained.

[0050] Here, examples of organic iron compounds capable of forming an iron thin film include iron pentacarbonyl, ferrocene, acetylacetonate iron (II), acetylacetonate iron (III), trifluoroacetylacetonate iron (II), trifluoroacetylacetonate iron (III), etc. Examples of iron salts capable of forming an iron thin film include inorganic iron acids such as iron sulfate, iron nitrate, iron phosphate, iron chloride, and iron bromide, and organic iron acids such as iron acetate, iron oxalate, iron citrate, and iron lactate. These iron compounds may be used alone or in combination.

[0051] The organic solvent contained in Coating Liquid B is not particularly limited, and for example, the organic solvents mentioned above as those usable in Coating Liquid A can be used.

[0052] The coating and drying of the above-mentioned coating liquid A and coating liquid B can be carried out by using a known method.

[0053] For example, coating liquid A can be applied to a substrate by a dip method. Specifically, the substrate can be immersed in coating liquid A, held therein, and then pulled up. Conditions such as the time for which the substrate is held in coating liquid A and the lifting speed when the substrate is lifted up from coating liquid A can be appropriately set within a range in which the desired effects of the present invention can be obtained. In the above-mentioned dip method, the substrate is immersed in coating liquid A, held therein, and then pulled up, and the angle formed between the surface direction of the coating liquid A and the surface direction of the substrate is not particularly limited, and can be, for example, 90° (right angle).

[0054] Furthermore, conditions such as temperature and drying time for drying the coating film of Coating Liquid A formed on the substrate can also be appropriately set within ranges that achieve the desired effects of the present invention.

[0055] The aluminum thin film formed on the substrate may have a thickness of, for example, 10 nm or more and 100 nm or less. The thickness of the thin aluminum film can be adjusted by, for example, the pulling speed when pulling the substrate out of the coating solution A.

[0056] Furthermore, for example, coating of Coating Liquid B onto an aluminum thin film formed on a substrate can be carried out by a dipping method. Specifically, the substrate on which the aluminum thin film has been formed can be immersed in Coating Liquid B, and then held and pulled up. In the above-mentioned dipping method in which the substrate is immersed in Coating Liquid B, held, and pulled up, the angle between the surface direction of Coating Liquid B and the surface direction of the substrate is not particularly limited, and can be, for example, 90° (a right angle).

[0057] Here, the time for which the substrate on which the aluminum thin film has been formed is held in Coating Liquid B can be, for example, from 5 seconds to 60 seconds.

[0058] The lifting speed when the substrate on which the aluminum thin film is formed is lifted from the coating liquid B is preferably 1 mm / sec or more, more preferably 2 mm / sec or more, even more preferably 3 mm / sec or more, preferably 18 mm / sec or less, more preferably 12 mm / sec or less, and even more preferably 8 mm / sec or less. If the lifting speed from the coating liquid B is equal to or higher than the lower limit, the thickness of the formed iron thin film can be appropriately increased, and the predetermined localized electron amount of the fibrous carbon nanostructure to be manufactured can be appropriately reduced. On the other hand, if the lifting speed from the coating liquid B is equal to or lower than the upper limit, the thickness of the formed iron thin film can be appropriately reduced, and the predetermined localized electron amount of the fibrous carbon nanostructure to be manufactured can be appropriately increased. Therefore, if the lifting speed when the substrate on which the aluminum thin film is formed is lifted from the coating liquid B within the above-mentioned predetermined range, the formed iron thin film can be made to have an appropriate thickness, and the localized electron amount of the fibrous carbon nanostructure to be manufactured can be easily kept within the above-mentioned predetermined range.

[0059] The conditions such as temperature and drying time when drying the coating film of Coating Liquid B formed on the aluminum thin film can be appropriately set within a range in which the desired effects of the present invention can be obtained.

[0060] The thickness of the iron thin film formed on the aluminum thin film is preferably 0.5 nm or more, more preferably 1 nm or more, even more preferably 2 nm or more, and preferably 4.5 nm or less, more preferably 4 nm or less, and even more preferably 3.5 nm or less. If the thickness of the iron thin film is equal to or greater than the lower limit, the predetermined localized electron amount of the fibrous carbon nanostructure to be manufactured can be appropriately reduced. On the other hand, if the thickness of the iron thin film is equal to or less than the upper limit, the predetermined localized electron amount of the fibrous carbon nanostructure to be manufactured can be appropriately increased. Therefore, if the thickness of the iron thin film is within the above-mentioned predetermined range, the predetermined localized electron amount of the fibrous carbon nanostructure to be manufactured can be easily kept within the above-mentioned predetermined range. The thickness of the thin film can be adjusted by, for example, the lifting speed when lifting the substrate on which the aluminum thin film has been formed from Coating Liquid B.

[0061] (Method for producing surface-modified fibrous carbon nanostructures) The method for producing a surface-modified fibrous carbon nanostructure of the present invention is characterized by comprising a step of subjecting the above-mentioned fibrous carbon nanostructure of the present invention to a surface modification treatment to obtain a surface-modified fibrous carbon nanostructure (surface modification treatment step). According to the method for producing a surface-modified fibrous carbon nanostructure of the present invention, it is possible to produce a surface-modified fibrous carbon nanostructure with excellent dispersibility. The method for producing a surface-modified fibrous carbon nanostructure of the present invention may optionally include a step other than the above surface modification treatment step.

[0062] <Surface modification process> In the surface modification step, the fibrous carbon nanostructure is subjected to a surface modification treatment to obtain a surface-modified fibrous carbon nanostructure. Here, the surface modification treatment is not particularly limited, and for example, a wet treatment or a dry treatment can be used. The wet treatment can be carried out using a surface modifying agent such as nitric acid, sulfuric acid, a mixed acid of nitric acid and sulfuric acid, hydrogen peroxide, etc. The dry treatment can be carried out using a surface modifying agent such as oxygen, ozone, fluorine gas, etc. Among these, from the viewpoint of obtaining a surface-modified fibrous carbon nanostructure having even more excellent dispersibility, the surface modification treatment is preferably a wet oxidation treatment carried out using nitric acid, sulfuric acid, or a mixed acid of nitric acid and sulfuric acid. The conditions for the surface modification treatment can be set depending on the type of surface modification agent used and the desired properties of the surface-modified fibrous carbon nanostructure.

[0063] <Surface-modified fibrous carbon nanostructures> The surface-modified fibrous carbon nanostructure obtained by subjecting the fibrous carbon nanostructure of the present invention to a surface modification treatment can be well dispersed in a solvent such as water without the use of a dispersant. The resulting dispersion of the surface-modified fibrous carbon nanostructure can be used to manufacture various molded products (for example, films such as antistatic films and conductive films). Here, in the dispersion of the surface-modified fibrous carbon nanostructure, the surface-modified fibrous carbon nanostructure is well dispersed in the solvent, so that the amount of agglomerates can be reduced in the molded article produced using the dispersion. Therefore, the molded article made of the surface-modified fibrous carbon nanostructure produced has excellent properties such as electrical conductivity, thermal conductivity, and strength. In other words, it can be said that the surface-modified carbon nanostructure has excellent properties as described above. EXAMPLES

[0064] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following, "%" representing an amount is based on mass unless otherwise specified.

[0065] In the examples and comparative examples, the G / D ratio, average diameter, BET specific surface area, t-plot, total specific surface area, internal specific surface area, carbon purity, and amount of localized electrons of the fibrous carbon nanostructure containing CNT, and the dispersibility after the surface modification treatment were measured or evaluated by the following methods, respectively.

[0066] <G / D ratio> Using a microscopic laser Raman system (manufactured by Thermo Fisher Scientific Co., Ltd., Nicolet Almega XR), measurement was performed on the fibrous carbon nanostructure near the center of the substrate.

[0067] <Average diameter> The diameters (outer diameters) of 20 fibrous carbon nanostructures randomly selected from the images obtained using a transmission electron microscope were measured and the number average value was determined.

[0068] <BET specific surface area, t-plot, total specific surface area and internal specific surface area> Measurement was performed using a BET specific surface area measuring device (manufactured by Nippon Bell Co., Ltd., BELSORP (registered trademark)-mini).

[0069] <Carbon purity> Using a thermogravimetric analyzer (TG), the carbon purity (= (mass reduced by combustion until reaching 800 °C / initial mass) × 100 (%)) was determined from the mass reduction when the fibrous carbon nanostructure was heated to 800 °C in air.

[0070] <Amount of localized electrons> Using an electron spin resonance apparatus (Elexsys E580 manufactured by BRUKER), with copper sulfate pentahydrate as a standard sample, the amount of localized electrons of the fibrous carbon nanostructure was quantified from the ratio of the signal intensity at a temperature of 10 K to the sample weight.

[0071] <Dispersibility after surface modification treatment> <<Evaluation of dispersion liquid>> The dispersion of the surface-modified fibrous carbon nanostructures was centrifuged at 20,000G for 40 minutes using a centrifuge (manufactured by Beckman Coulter, product name "OPTIMA XL100K"), and the cycle of collecting the supernatant was repeated three times to obtain 20 mL of the dispersion of the surface-modified fibrous carbon nanostructures after centrifugation. The presence or absence of agglomerates in this dispersion was confirmed by visual observation. If no agglomerates were observed by visual observation, this indicates that the fibrous carbon nanostructures have excellent dispersibility after the surface modification treatment.

[0072] In addition, the particle size of the particles present in the dispersion after the above-mentioned centrifugation treatment was measured using a dynamic light scattering (DLS) particle size distribution analyzer (manufactured by Malvern, product name "Zetasizer Nano ZS") to evaluate the dispersibility of the surface-modified fibrous carbon nanostructures. Note that the smaller the particle size, the better the surface modification of the fibrous carbon nanostructures is, indicating that the dispersibility after the surface modification treatment is excellent.

[0073] <<Evaluation of Molded Products (Films)>> In addition, the dispersion of the surface-modified fibrous carbon nanostructure was applied to a glass substrate using a bar coater #2, and then dried at 130°C for 10 minutes to form a film of the surface-modified fibrous carbon nanostructure on the glass substrate. The obtained film was then observed under an optical microscope (magnification 100 times) to check for the presence or absence of agglomerates (diameter 30 μm or more) of the surface-modified fibrous carbon nanostructure visible in the field of view of the microscope, thereby evaluating the dispersibility of the surface-modified fibrous carbon nanostructure. If no agglomerates of the surface-modified fibrous carbon nanostructure are observed in the field of view of the microscope, this indicates that the fibrous carbon nanostructure has been well surface-modified and has excellent dispersibility after the surface modification treatment.

[0074] <<Overall rating>> If there were no agglomerates in the dispersion of the surface-modified fibrous carbon nanostructure, the particle diameter measured using a dynamic light scattering (DLS) particle size distribution analyzer was 180 nm or less, and there were no agglomerates in the film, the result was rated as "excellent," and all other cases were rated as "unacceptable."

[0075] Example 1 <Production of catalyst substrate> Aluminum tri-sec-butoxide was dissolved in 2-propanol to prepare coating solution A. Iron acetate was dissolved in 2-propanol to prepare coating solution B.

[0076] The above-mentioned coating liquid A was applied to the surface of a stainless steel substrate as a flat substrate to form an alumina thin film (catalyst-supported layer) with a thickness of 40 nm. Next, the above-mentioned coating liquid B was applied to the alumina thin film provided on the substrate by a dipping method at a lifting speed of 5 mm / sec to obtain a substrate (catalyst substrate) having a thin iron film with a thickness of 2 nm as a catalyst layer.

[0077] <Synthesis of fibrous carbon nanostructures> An oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures including CNTs) was synthesized by successively carrying out a formation process (reduction process), a synthesis process, and a cooling process on the above-mentioned catalyst substrate. In the formation process, hydrogen gas was supplied to the catalyst substrate to carry out a reduction treatment. In the synthesis process, raw material gas (including ethylene gas, nitrogen gas as a carrier gas, and water as an activator) was supplied to the catalyst substrate.

[0078] The obtained fibrous carbon nanostructure containing CNTs had a G / D ratio of 3.8, an average diameter of 4 nm, and a BET specific surface area of ​​1446 cm 2 / g, the carbon purity is 99.9%, and the Raman spectrophotometer measurement shows a 100-300 cm peak characteristic of single-walled carbon nanotubes. -1 A radial breathing mode (RBM) peak was observed in the low wavenumber region of 100 nm. The t-plot of the fibrous carbon nanostructure obtained from the adsorption isotherm was bent in an upward convex shape. The bending point was at t = 0.7 nm, and the total specific surface area S1 was 970 m 2 / g, and the internal specific surface area S2 is 170 m 2 / g, and S2 / S1 was 0.18. Furthermore, the amount of localized electrons in the obtained fibrous carbon nanostructure containing CNTs at a temperature of 10 K was 5.6 × 10 18 It was 1 / g.

[0079] <Preparation of dispersion of surface-modified fibrous carbon nanostructures> A 300 mL flask equipped with a cooling tube and stirring blade was charged with 0.80 g of the fibrous carbon nanostructure containing CNT obtained above, 54.8 g of ion-exchanged water, and 83 mL of a mixed acid solution containing sulfuric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration 96-98%) and nitric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration 69-70%) in a 1:3 (volume ratio), and then the mixture was heated with stirring at an internal temperature of 110°C for 8 hours, thereby performing a mixed acid treatment as a wet oxidation treatment.

[0080] 3.0 g of the resulting fibrous carbon nanostructure / mixed acid solution after the mixed acid treatment was weighed into a 50 mL sample bottle and diluted with 27.0 g of ion-exchanged water. After removing the supernatant, ion-exchanged water was added to make the liquid volume 30 mL. After adding 0.1% ammonia water to adjust the pH to 7.0, ultrasonic irradiation was performed at a frequency of 42 Hz for 50 minutes using an ultrasonic irradiation device (manufactured by Branson, product name "BRANSON5510") to obtain a dispersion of surface-modified fibrous carbon nanostructures.

[0081] The obtained dispersion of the surface-modified fibrous carbon nanostructure was used to evaluate the dispersibility of the fibrous carbon nanostructure after the surface modification treatment. The results are shown in Table 1.

[0082] Example 2 The synthesis of fibrous carbon nanostructures and the preparation of a dispersion of surface-modified fibrous carbon nanostructures were carried out under the same conditions as in Example 1, except that the thickness of the formed iron thin film was changed from 2 nm to 3 nm by changing the pull-up speed when coating liquid B on the alumina thin film provided on the substrate from 5 mm / sec to 10 mm / sec. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The obtained fibrous carbon nanostructure containing CNTs had a G / D ratio of 2.9, an average diameter of 4 nm, and a BET specific surface area of ​​1191 cm. 2 / g, the carbon purity is 99.9%, and the Raman spectrophotometer measurement shows a 100-300 cm peak characteristic of single-walled carbon nanotubes. -1A radial breathing mode (RBM) peak was observed in the low wavenumber region of 100 nm. The t-plot of the fibrous carbon nanostructure obtained from the adsorption isotherm was bent upward in a convex shape. The bending point was at t = 0.7 nm, and the total specific surface area S1 was 840 m 2 / g, and the internal specific surface area S2 is 70m 2 / g, and S2 / S1 was 0.08. Furthermore, the amount of localized electrons in the obtained fibrous carbon nanostructure containing CNTs at a temperature of 10 K was 9.9 × 10 17 It was 1 / g. In addition, the dispersion of the obtained surface-modified fibrous carbon nanostructures was used to evaluate the dispersibility of the fibrous carbon nanostructures after the surface modification treatment. The results are shown in Table 1.

[0083] Example 3 The synthesis of fibrous carbon nanostructures and the preparation of a dispersion of surface-modified fibrous carbon nanostructures were carried out under the same conditions as in Example 1, except that the thickness of the formed iron thin film was changed from 2 nm to 4 nm by changing the pull-up speed when coating liquid B on the alumina thin film provided on the substrate from 5 mm / sec to 15 mm / sec. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The obtained fibrous carbon nanostructure containing CNTs had a G / D ratio of 1.9, an average diameter of 4 nm, and a BET specific surface area of ​​1104 cm. 2 / g, the carbon purity is 99.9%, and the Raman spectrophotometer measurement shows a 100-300 cm peak characteristic of single-walled carbon nanotubes. -1 A radial breathing mode (RBM) peak was observed in the low wavenumber region of 1000 nm. The t-plot of the fibrous carbon nanostructure obtained from the adsorption isotherm was bent in an upward convex shape. The bending point was at t = 0.7 nm, and the total specific surface area S1 was 800 m 2 / g, and the internal specific surface area S2 is 40m 2 / g, and S2 / S1 was 0.05. Furthermore, the amount of localized electrons in the obtained fibrous carbon nanostructure containing CNTs at a temperature of 10 K was 4.9 × 10 17 It was 1 / g. In addition, the dispersion of the obtained surface-modified fibrous carbon nanostructures was used to evaluate the dispersibility of the fibrous carbon nanostructures after the surface modification treatment. The results are shown in Table 1.

[0084] Comparative Example 1 The synthesis of fibrous carbon nanostructures and the preparation of a dispersion of surface-modified fibrous carbon nanostructures were carried out under the same conditions as in Example 1, except that the thickness of the formed iron thin film was changed from 2 nm to 5 nm by changing the pull-up speed when coating liquid B on the alumina thin film provided on the substrate from 5 mm / sec to 20 mm / sec. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The obtained fibrous carbon nanostructure containing CNTs had a G / D ratio of 3.5, an average diameter of 4 nm, and a BET specific surface area of ​​1113 cm. 2 / g, the carbon purity is 99.9%, and the Raman spectrophotometer measurement shows a 100-300 cm peak characteristic of single-walled carbon nanotubes. -1 A radial breathing mode (RBM) peak was observed in the low wavenumber region of 1000 nm. The t-plot of the fibrous carbon nanostructure obtained from the adsorption isotherm was bent upward in a convex shape. The bending point was at t = 0.7 nm, and the total specific surface area S1 was 1120 m 2 / g, and the internal specific surface area S2 is 120m 2 / g, and S2 / S1 was 0.11. Furthermore, the amount of localized electrons in the obtained fibrous carbon nanostructure containing CNTs at a temperature of 10 K was 8.4 × 10 16 It was 1 / g. In addition, the dispersion of the obtained surface-modified fibrous carbon nanostructures was used to evaluate the dispersibility of the fibrous carbon nanostructures after the surface modification treatment. The results are shown in Table 1.

[0085] Comparative Example 2 As an oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs), a dispersion of surface-modified fibrous carbon nanostructures was prepared using Meijo Nano Carbon's "e-DIPS," which is a single-walled carbon nanotube, and the dispersibility after surface modification was evaluated. The results are shown in Table 1. In addition, in the obtained dispersion of surface-modified fibrous carbon nanostructures, the surface-modified fibrous carbon nanostructures formed extremely large agglomerates, so the particle size could not be measured and a film could not be formed. The "e-DIPS" manufactured by Meijo Nano Carbon Co., Ltd. used above has a BET specific surface area of ​​900 cm 2 / g, and the amount of localized electrons at a temperature of 10 K is 4.0×10 16 The number was less than particles / g (below the detection limit).

[0086] [Table 1]

[0087] It is clear from Table 1 that the fibrous carbon nanostructures of Examples 1 to 3, in which the amount of localized electrons obtained by electron spin resonance measurement at a temperature of 10 K is equal to or greater than a predetermined value, have excellent dispersibility after surface modification treatment. On the other hand, the fibrous carbon nanostructures of Comparative Examples 1 and 2, in which the amount of localized electrons obtained by electron spin resonance measurement at a temperature of 10 K is less than the predetermined value, are found to have poor dispersibility after the surface modification treatment. [Industrial Applicability]

[0088] According to the present invention, it is possible to provide a fibrous carbon nanostructure having excellent dispersibility after surface modification treatment. Furthermore, according to the present invention, it is possible to provide a surface-modified fibrous carbon nanostructure having excellent dispersibility.

Claims

1. The amount of localized electrons obtained by electron spin resonance measurement at a temperature of 10 K is 5.6 × 10 / g or more, A fibrous carbon nanostructure in which a t-plot obtained from an adsorption isotherm shows an upwardly convex shape.

2. The amount of localized electrons obtained by electron spin resonance measurement at a temperature of 10 K is 5.6 x 10 18 / g or more, A fibrous carbon nanostructure having a ratio of G band peak intensity to D band peak intensity (G / D ratio) in a Raman spectrum of 0.5 or more and 5.0 or less.

3. The amount of localized electrons is 1.0×10 19 The fibrous carbon nanostructure according to claim 1 or 2, wherein the number of nanoparticles per gram is less than one.

4. The fibrous carbon nanostructure according to any one of claims 1 to 3, comprising a carbon nanotube.

5. The fibrous carbon nanostructure of claim 4 , wherein said carbon nanotubes comprise single-walled carbon nanotubes.

6. A method for producing a surface-modified fibrous carbon nanostructure, comprising the step of subjecting the fibrous carbon nanostructure according to any one of claims 1 to 5 to a surface modification treatment to obtain a surface-modified fibrous carbon nanostructure.

7. The method for producing a surface-modified fibrous carbon nanostructure according to claim 6 , wherein the surface modification treatment is a wet oxidation treatment.

Citation Information

Patent Citations

  • Method for producing carbon fiber

    JP2003013330A

  • Finely graphitized carbon fiber, method for producing the same and use for the same

    JP2004143652A

  • Polyacrylonitrile-based polymer and method for producing the same, and method for producing carbon fiber precursor, and carbon fiber and method for producing the same

    JP2008248219A

  • Fluorination of multilayer carbon nanomaterials

    JP2009515813A

  • Metal matrix composite and production method thereof

    JP2016183395A